ajudem aii
![50 + (3x - 4) = 2.(3x - 4) + 26 50 + (3x - 4) = 2.(3x - 4) + 26](https://tex.z-dn.net/?f=50+%2B+%283x+-+4%29+%3D+2.%283x+-+4%29+%2B+26+)
Soluções para a tarefa
Respondido por
0
Resposta:
x= 12
Explicação passo-a-passo:
Respondido por
0
Resposta:
x = 28/3
Explicação passo-a-passo:
50 + (3x - 4) = 2.(3x - 4) + 26
(3x - 4) - 2(3x - 4) = 26 - 50
(1 - 2) × (3x - 4) = 26 - 50
- 1(3x - 4) = 26 - 50
3x- 4 = 26 - 50
3x - 4 = 24
3x = 24 + 4
3x = 28
x = 28/3
Boas lições.
eduardo0208:
está errado
Perguntas interessantes